Reflecting on Earlier Experiences with Unsolicited Findings: Points to Consider for Next‐Generation Sequencing and Informed Consent in Diagnostics. Issue 10 (16th July 2013) - Rigter, Tessel; Henneman, Lidewij; Kristoffersson, Ulf; Hall, Alison; Yntema, Helger G.; Borry, Pascal; Tönnies, Holger; Waisfisz, Quinten; Elting, Mariet W.; Dondorp, Wybo J.; Cornel, Martina C.
<x xml:space="preserve">Abstract</x> High‐throughput nucleotide sequencing is increasingly being used in clinical diagnostics. The increased chance of detecting unsolicited findings requires decisions on disclosure of these findings and poses a challenge for the informed consent procedure. This article discusses the ethical and practical dilemmas encountered when contemplating informed consent for next generation sequencing in diagnostics from a multidisciplinary point of view. We hereby aim to provide a sound basis for developing guidelines for optimizing the informed consent procedure<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>